Analisis Pengaruh Bermain Games (Ms.Windows) pada Saat Jam Istirahat Siang terhadap Kinerja dengan Menggunakan Rantai Markov dan Uchida Kraepelin Test - ., Andrijanto; Yuliana, Evelyn (Zenit, 2012)
Employees might experience boredom while facing the same  situation and job while working  with the computer. Playing a computer game can be an alternative to recover from that condition, but playing a game during the office hours is prohibited. That activity is assumed have a bad effect on their performance. To play a game in the office, some employees do it at lunch time, but they do not have many game options. In the office computer, there are only Microsoft Windows games, built in Windows program package. This research is done to find out the effect of playing Microsoft games at lunch time on the employee performance. This research will make a behavior analysis as well  as performance  analysis.  Behaviour analysis is done to find  out  the  probability of people selecting one game then moving/changing to another game. This analysis will give a segmentation on Microsoft games to find out, which game is the most favorite. Markov Chain is used to analyze the behaviour. Performance analysis is done to find out the effect of game resulted from behaviour analysis to the performance. The performace is a cognitive ability of employees. Uchida Kraepelin  Test  (UKT) is used to measure a cognitive ability. Performance  criteria are the maximum total job and the total error of job. The job will be a simple additional task performed by UKT. Thirty employees with the same habit in playing Microsoft game during lunch time in the office are observed to study the behavior. Four male employees from Divisi Desain Grafis Perusahaan X, ages between 22 –  24 years old, have the same job and  same  working  place will be an object  for  performance  test. The result from the behaviour analysis will be tested for the four male employees. Besides, which game will give a good effect on the performance will be analyzed. The games include  Solitaire, Spider Solitaire, dan Minesweeper. The data from UKT measurement is tested by one way ANOVA, 2 way interaction ANOVA, Goodness of Fit test, T-test, dan Principal Components Analysis (PCA). One way ANOVA shows that after playing games the performance is not descending, 2 way interaction ANOVA shows that the variance on game effected on the  max total job can be done, it does not affect on the total errors of job. Besides, the duration of playing a game does not affect the max total job and the total errors of  job. T-test and PCA show that Minesweeper game gives a very good effect on the performance.Keywords: Markov Chain, Uchida Kraepelin Test, Ergonomy Cognitive, Performance